ANALISIS PENGARUH ASPEK KEPERILAKUAN TERHADAP PENGGUNAAN SISTEM AKUNTANSI (Studi Pada PT. Bank X Tbk di Wilayah Kota dan Kabupaten Jayapura) - Budianto Ngo; Siti Rofingatun; Mariolin Sanggenafa (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2019)
This study aims to determine the effect of attitudes towards the use of accounting systems at PT. Bank Mandiri in the city and district of Jayapura, to determine the effect of motivation on the use ofaccounting systems at PT. Bank Mandiri in the city and district of Jayapura, to determine the effect of emotions on system usage accounting at PT. Bank Mandiri in the city and district of Jayapura, todetermine the effect of the perception of the use of the accounting system at PT. Bank Mandiri in the city and Jayapura area. This study is a correlational study or the relationship between the independentvariables on the dependent variable and the analysis unit that is considered to be employees who have worked more than 6 months who have undergone a training period of 40 people. The questionnairetested its validity and reliability before testing the research data, the test equipment used in this study used the classical assumption test which included normality test, linearity test, heteroscedasticity testand multicollinearity test, the data analysis method used was multiple linear regression analysis using a tool of analysis in SPSS 25 statistics. The results of this study indicate that attitude variables do notsignificantly influence the use of accounting systems, the motivation variable does not significantly influence the use of accounting systems, emotional variables have a significant effect on the use of accounting systems and perception variables do not significantly influence the use of accountingsystems.